Influence of Lithium Ion Kinetics, Particle Morphology and Voids on the Electrochemical Performance of Composite Cathodes for All-Solid-State Batteries. Issue 2 (1st February 2022) - Bielefeld, Anja; Weber, Dominik A.; Rueß, Raffael; Glavas, Vedran; Janek, Jürgen
Abstract : With the ongoing transformation to e-mobility, lithium all-solid-state batteries are promising candidates for advanced mobile energy storage. Other than in conventional lithium ion cells, the rigid solid electrolyte entails its own morphology and does not wet residual voids in composite electrodes, which can limit the cell performance. We therefore take a closer look at the influence of microstructural characteristics on different scales in composite cathodes by means of electrochemical simulation using the finite element method. Cathode active material particle arrangements are constructed to validate the model against experimental data. We highlight the significance of the active material particle size distribution and state-of-charge dependent input parameters, such as the lithium diffusion coefficient in NCM811 and the exchange current density at the interface of NCM811 and Li6 PS5 Cl. We zoom in on that interface under the presence of void space that can result from manufacturing or arise from inter-particle contact loss upon volume changes. In a 1-particle-void model, the impact of the active surface area covered by voids is studied as well as the influence of the void distribution and the void size on the electrochemical performance. Beyond that, we simulate a tortuosity-optimized structured electrode and provide first guidelines for laser-patterned all-solid-state cathodes.